Pemberian Jus Mentimun (Cucumis Sativus Linn) Pada Penderita Hipertensi Wanita Usia Produktif - Zul Fikar Ahmad; Siti Surya Indah Nurdin (Journal Syifa Sciences and Clinical Research, 2019)
Hypertension is one of the public health problems that cause mortality and inability to reach life expectancy. The aim of the research is to assess the effect of juice cucumber (Cucumis sativus Linn) on blood pressure of hypertension patients. The research used a quasi experiment design with Non-Randomized Control Group Pre-test Post-test Design. The populations include pre-hypertension and hypertension grade I patients of women childbearing age in the working area of Telaga Biru Health Centre of Gorontalo Regency. The samples were 42 pre-hypertension and hypertension grade I patients. They were divided into two groups, a group given cucumber juice without seeds and another group given cucumber juice with seeds. The data were analyzed using Paired-samples t Test and Independent-samples t Test. The result of the study indicate that giving cucumber juice without seeds decrease of systolic blood pressure by 18,524 mmHg (p = 0,000) and decrease diastolic blood pressure by 8,905 mmHg (p = 0,000). Giving cucumber juice with seeds could decrease systolic blood pressure by 15,952 mmHg (p = 0,000) and diastolic blood pressure by 7,571 mmHg (p = 0,000). There was no difference between giving cucumber juice without seeds and giving cucumber juice with seeds in the decrease of systolic blood pressure (p = 0,257) and the decrease of diastolic blood pressure (p = 0,414). This shows that giving cucumber juice can decrease blood pressure.